Antidiabetic Activity of Ethanolic Extract of Kale (Brassica oleracea var. sabellica) - Afdrian Kusumawardianingrum; Novena Yety Lindawati (Faculty of Pharmacy, Universitas Airlangga, 2022)
Background: Diabetes Mellitus is a disease caused by a disruption of the pancreas in producing insulin. The International Diabetes Federation (IDF) organization identified ten countries that have the highest cases of Diabetes Mellitus. Indonesia is ranked 7th out of 10 countries and is the only Southeast Asian country included in the list. Prevention of diabetes mellitus is a solution that must be done to reduce cases of diabetes mellitus in Indonesia., one of which is by consuming vegetables that have antidiabetic activity. Objective: This study was conducted to determine the activity of kale (Brassica oleracea var. sabellica) extract in reducing glucose levels. Methods: The qualitative test results showed that the kale extract contained positive flavonoids, triterpenoids, tannins and phenols. The antidiabetic activity test was carried out using the UV-Vis spectrophotometer and the Nelson Somogyi method. This test is carried out at the 25th minute operating time and a maximum λ of 745 nm. Results: The decrease in glucose levels in kale extract concentration of 4 ppm was 2.23% ± 0.46, 6 ppm of 16.47% ± 0.27.8 ppm of 30.62% ± 0.46, 10 ppm of 41.88 ± 0.27, 12 ppm of 55.50 ± 0.20. The concentration of kale extract in reducing glucose up to 50% (EC50) was 11.13 ppm. Conclusion: Kale extract (Brassica oleracea var. sabellica) can reduce glucose levels or have antidiabetic activity.